2003
DOI: 10.1083/jcb.200304159
|View full text |Cite
|
Sign up to set email alerts
|

Akt activation disrupts mammary acinar architecture and enhances proliferation in an mTOR-dependent manner

Abstract: Activation of the serine/threonine kinase Akt/PKB positively impacts on three cellular processes relevant to tumor progression: proliferation, survival, and cell size/growth. Using a three-dimensional culture model of MCF-10A mammary cells, we have examined how Akt influences the morphogenesis of polarized epithelial structures. Activation of a conditionally active variant of Akt elicits large, misshapen structures, which primarily arise from the combined effects of Akt on proliferation and cell size. Importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
153
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(167 citation statements)
references
References 53 publications
14
153
0
Order By: Relevance
“…However, these mutant PI3K isoforms did not lead to a significant disruption in adherent cell junction formation as visualised by peripheral ZO-1 staining (Figure 4d). In MCF10A cells, over-expression of either HER2 or activated AKT leads to aberrant proliferation, luminal cell survival and disruption of acinar architecture [26,27]. In contrast, we found that in NMuMG cells, neither expression of AKT1 E17K, nor over-expression of HER2 had a significant effect either on 3D lumen formation or adherent cell junction formation ( Figure 4g-k).…”
Section: Mammary Epithelial Cell Transformation By P110α Akt1 Her2 mentioning
confidence: 78%
See 1 more Smart Citation
“…However, these mutant PI3K isoforms did not lead to a significant disruption in adherent cell junction formation as visualised by peripheral ZO-1 staining (Figure 4d). In MCF10A cells, over-expression of either HER2 or activated AKT leads to aberrant proliferation, luminal cell survival and disruption of acinar architecture [26,27]. In contrast, we found that in NMuMG cells, neither expression of AKT1 E17K, nor over-expression of HER2 had a significant effect either on 3D lumen formation or adherent cell junction formation ( Figure 4g-k).…”
Section: Mammary Epithelial Cell Transformation By P110α Akt1 Her2 mentioning
confidence: 78%
“…In these models, several types of primary and immortal mammary epithelial cells give rise to spherical colonies with a single hollow lumen. However, in separate studies, cells lacking PTEN [24], expressing oncogenic mutants of p110 [25] or AKT1 [26], or over-expressing HER2 [27], have each been found to display aberrant tissue architecture and fail to form a single hollow lumen. On the other hand, expression of mutant AKT1 E17K from the endogenous gene in engineered MCF10A cells did not cause morphological changes, in contrast to mutant PIK3CA expression [28].…”
Section: Introductionmentioning
confidence: 99%
“…The Spearman rank correlation analysis showed very 5 The IHC score of phosphorylated Akt, BAD and caspase-9 in breast tumors was stratified into low (negative-moderate) and high (strong) for the analysis. significant correlations between NOS2 and COX2 expression, and the phosphorylation of Akt, BAD, and caspase-9.…”
Section: Akt Pathway Activation In Relationship To Markers Of Inflammmentioning
confidence: 99%
“…1,2 The 3 closely related Akt isoforms induce cell proliferation and soft agar growth, and disrupt the acinar architecture of human mammary cells, but do not induce transformation by themselves. [3][4][5] Akt activation requires 2 critical phosphorylation steps at Thr308 and Ser473. The phosphorylation is induced by ligand-mediated activation of growth factor receptors and receptor tyrosine kinases.…”
mentioning
confidence: 99%
“…One explanation may relate to the suppression of both p53 and p21. AKT is known to promote the cytoplasmic localization of p21 and promote nuclear translocation of Mdm2, a negative regulator of p53, thereby causing a reduction in p53 transactivation and levels (Debnath et al, 2003).…”
Section: Discussionmentioning
confidence: 99%